Anthropometric, fitness and technical skill characteristics of elite male national soccer players: A review - Strauss, A.; Jacobs, S.; Van den Berg, L. (African Journal for Physical, Health Education, Recreation and Dance, 2012)
Soccer is the most popular sport in the world. Performance at optimal levels requires high levels of technical, tactical and physiological skills. Identification and selection of talented soccer players are not straightforward procedures. Anthropometric, physiological and skill attributes may contribute to select talented players. The selection made at early ages may be relevant up until adulthood and many players may drop out of soccer only because of their date of birth. Team sport coaches thus have the dilemma of balancing the development of skill and physiological requirements of the players. Soccer requires superior levels of both aerobic and anaerobic fitness. Optimal aerobic fitness is a prerequisite for elite soccer players and has benefits such as increased work intensity during a game; prevention of a second-half reduction in performance; doubling the number of sprints completed; and allowing players to cover a greater distance. The players` aerobic capacity plays an important role in modern soccer and also has a major influence on their technical performance. Muscle strength, power and speed are important physiological characteristics in order to perform sprinting, jumping, tackling and kicking in soccer. Anaerobic activity may constitute the more crucial moments of the game and contribute directly to winning possession of the ball and to the scoring and conceding of goals. This review summarises and provides an update of data available on the physiology of male soccer players representing different countries worldwide. The information may have important implications for the success of soccer players and teams and could guide coaches in the selection process.